Fabricating Industry‐Compatible Olefin‐Linked COF Resins for Oxoanion Pollutant Scavenging. (24th November 2022) - Zhang, Penghui; Wang, Zhifang; Wang, Sa; Wang, Jian; Liu, Jinjin; Wang, Ting; Chen, Yao; Cheng, Peng; Zhang, Zhenjie
Abstract: Large‐scale and low‐cost synthesis of covalent organic frameworks (COFs) to meet the demands of industrial application remains formidably challenge. Here we report using 2, 4, 6‐collidine as monomer to produce a series of highly crystalline olefin‐linked COFs by a melt polymerization method. This method enables the kilogram‐scale fabrication of self‐shaped monolithic robust foams. The afforded COFs possess extremely low cost (<50 USD/kg), superior to all the reported COFs. Furthermore, using one‐pot or post‐modification methods can conveniently transform neutral COFs to ionic COFs, which can be applied as highly efficient ion‐exchange sorbents for scavenging oxoanion pollutants. Remarkably, the superior adsorption capacity of a model oxoanion (ReO4 − ) is the highest among crystalline porous materials reported so far. This work not only expands the scopes of olefin‐linked COFs but also enlightens the route for the industrial production of crystalline ion exchange sorbents. Abstract : Neutral and ionic vinylene‐linked covalent organic frameworks (COFs) were constructed with inexpensive 2, 4, 6‐collidine as the building unit by a melt polymerization method. The as‐prepared, low‐cost cationic COF foams showed high crystallinity, abundant porosity, superior stability, and high adsorption capacity for oxoanion pollutants. This study opens a pathway to large‐scale industrial production of ionic COFs.